(untitled) (Altre Modernità, 2014)
Emigration and exile are increasingly topical demographic phenomena, which in contemporary world tend to lose their distinguishing features. Narrative with its structural and linguistic choices offers an enlightening overview of geographical, emotive and expressive diasporic representations.